1994
DOI: 10.1139/x94-308
|View full text |Cite
|
Sign up to set email alerts
|

Relation between genetic diversity and pollution impact in a 1912 experiment with East European Pinussylvestris provenances

Abstract: Results are presented of genetic variation and growth decline due to pollution for 11 European populations, 1 Turkish population, and 1 Siberian population of Scots pine (Pinussylvestris L.) growing in a provenance experiment established in 1912 in Pulawy, southeastern Poland. Since 1966 this area has been subjected to acute pollution from a nitrogen-fertilizer factory emitting high levels of SO2, NOx, NH3, and other toxic compounds. A significant negative correlation was found between genotype polymorphism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 3 publications
1
28
0
1
Order By: Relevance
“…The habitats of Scots pine populations in the highlands show a scattered distribution [17]. Topographical features of the landscape that limit gene flow may narrow the genetic divergence and reduce the adaptive ability of trees [51]. Populations existing at the margin of the distribution may be seriously degraded, inbred and exposed to unknown random effects.…”
Section: Patterns Of Phenotypic Variation Across Different Environmentsmentioning
confidence: 99%
“…The habitats of Scots pine populations in the highlands show a scattered distribution [17]. Topographical features of the landscape that limit gene flow may narrow the genetic divergence and reduce the adaptive ability of trees [51]. Populations existing at the margin of the distribution may be seriously degraded, inbred and exposed to unknown random effects.…”
Section: Patterns Of Phenotypic Variation Across Different Environmentsmentioning
confidence: 99%
“…The major advantages of nuclear microsatellite markers are their lower sensitivity to the variation in population effective size and the possibility of assessing heterozygosity (Scotti et al 2006). Populations characterized by a narrow genetic basis are thought to be more sensitive to environmental changes or disease, leading to a decrease in productivity (Oleksyn et al 1994). Another benefit of studying simple sequence repeat (SSR) markers is their high ability of alleles' discriminations.…”
Section: Introductionmentioning
confidence: 99%
“…Several independent studies reported a positive relationship between the genetic polymorphism of trees and their tolerance to air pollution (Geburek et al 1987, Oleksyn et al 1994, Prus-Glowacki et al 2006). There was a significant Scots pine provenance variation in tolerance to air pollution in the vicinity of a nitrogen fertilizer plant in Poland (Oleksyn et al 1994). Radial increment together with crown defoliation proved to be appropriate indicators of pollution tolerance in Scots pine genetic field tests (Oleksyn et al 1994 The objective of our study was to develop a screening approach for genetic tolerance to industrial pollution in Scots pine.…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant Scots pine provenance variation in tolerance to air pollution in the vicinity of a nitrogen fertilizer plant in Poland (Oleksyn et al 1994). Radial increment together with crown defoliation proved to be appropriate indicators of pollution tolerance in Scots pine genetic field tests (Oleksyn et al 1994 The objective of our study was to develop a screening approach for genetic tolerance to industrial pollution in Scots pine. We assessed the relationship between the temporal variation in strength of genetic control of radial increment of the seed orchard clones and past pollutant emissions.…”
mentioning
confidence: 98%
See 1 more Smart Citation